Nitrate Induced Photooxidation of Phenol and o-Substituted Phenolic Compounds in Aqueous Solution - NADIA, KOUACHI; TAHAR, SEHILI (Asian Journal of Chemistry, 2010)
The excitation of nitrate ions at 313 nm in the presence of phenol, 2-chlorophenol or 2-methylphenol in aqueous solution produced a complex mixture of compounds. The photoproducts were identified by LC-MS. Nitration, hydroxylation and coupling reactions were found to be the principal chemical processes. Cl/OH, CH3/OH substituted and hydroxylated phenolic derivatives are formed in very small amount. In contrast with phenol, no nitroso derivative was detected by 2-chlorophenol and 2-methylphenol under the same reaction conditions. Both nitrosation and nitration are attributed to reactions of nitrogen oxides NO2• and N2O4. Nitration and nitrosation are favoured in acidic medium. Kinetic studies were compared by varying environmental parameters including substrate and NO3– concentrations, oxygen content, pH and ethanol. The influence of substituted phenols is investigated by comparing their initial rates of degradation. Degradation pathways involving •OH and NO2• radicals as reactive species are proposed.